In Vitro and In Vivo pro-apoptotic and chemosensitizing effects of alpha-tomatine on human prostate adenocarcinoma / Lee Sui Ting - Lee, Sui Ting (2013)
Alpha (α)-tomatine is a major saponin found in tomatoes (Lycopersicon esculentum). The present study investigates the molecular mechanisms by which α-tomatine exerts its anti-cancer effect on human prostatic adenocarcinoma cells. Treatment of human androgen-dependent LNCaP and androgen-independent PC-3 prostate cancer cells with α-tomatine resulted in a concentration-dependent inhibition of cell growth with a halfmaximal efficient concentration (EC50) value of 2.65 ± 0.1 μM and 1.67 ± 0.3 μM, respectively. PC-3 cells appear to be more sensitive to α-tomatine-induced growth inhibition compared to LNCaP cells. Importantly, α-tomatine treatment is also less cytotoxic to non-tumorigenic human liver WRL-68 and human prostatic epithelial RWPE-1 cells. Due to the higher sensitivity of PC-3 cells to α-tomatine and significant morbidity of metastatic androgen-independent prostate cancer, it is of interest to study in greater detail the mechanisms of action of α-tomatine in PC-3 cells. Results from the present study showed that the inhibitory effect of α-tomatine on PC-3 cell growth was mainly due to the induction of apoptosis via the inhibition of nuclear factor-kappa B (NF-κB) pathway. Alpha-tomatine suppresses both basal constitutive and tumor necrosis factor-alpha (TNF-α)-induced NF-κB activation. The suppression of NF-κB activation by α-tomatine occurs through the inhibition of Akt, leading to the inhibition of IκBα kinase (IKK) activity and subsequently suppression of NF-κB nuclear translocation in PC-3 cells. The inhibition of NF-κB signaling pathway by α-tomatine was accompanied by significant reduction in the expression of NF-κB-dependent antiapoptotic proteins. The anti-tumor study of α-tomatine against PC-3 cells was extended to subcutaneous xenograft and orthotopic mouse models. Intraperitoneal administration of α-tomatine significantly attenuates the growth of PC-3 cell tumors grown at both sites without significant body weight loss. In agreement to the in vitro data, analysis of tumor materials showed an increase in tumor cell apoptosis and a decrease in the basal nuclear localization of NF-κB p50 and p65. The present study further investigated the efficacy of α-tomatine in combination with low-dose of paclitaxel in PC-3 cells. Treatment with sub-toxic dose of α-tomatine in combination with low-dose paclitaxel resulted in a decrease in cell viability with concomitant increase in apoptosis in PC-3 cells but not in non-tumorigenic human prostatic epithelial RWPE-1 cells. Results from these in vitro experiments indicated that the induction of apoptosis by the combined treatment was accompanied by the inhibition of phosphatidylinositol-3-kinase (PI3K)/protein kinase B (Akt) pro-survival signaling, which is an upstream mediator of NF-κB and known to confer chemoresistance in prostate cancer. The combined treatment also completely suppressed subcutaneous tumor growth in mouse xenograft without apparent body weight loss. Analysis of tumor materials showed an increase in tumor cell apoptosis with a reduction in the protein expression of activated PI3K/Akt. In summary, results from the present study provide comprehensive evidence that α- tomatine is an effective naturally-derived anti-tumor agent against androgenindependent prostate cancer and when used in combination, it can enhance the efficacy of taxane-based agent. The clinical applications of α-tomatine in prostate cancer treatment should be further explored.